2020
DOI: 10.1371/journal.pone.0236354
|View full text |Cite
|
Sign up to set email alerts
|

Energy-saving and pricing decisions in a sustainable supply chain considering behavioral concerns

Abstract: With the rising environmental concerns among consumers all over the world, sustainability has received considerable attention, and numerous enterprises are adopting various practices such as investing in energy-saving to improve sustainability in supply chains. However, many previous researches always assume that decision makers are perfectly rational and neglect the behavioral concerns of decision makers. This paper considers a two-stage sustainable supply chain with behavioral concerns in order to develop mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Some advanced technologies are relevant to the renewable energy sector for power generation to achieve optimal efficiency in the renewable energy supply chain, notably the Hybrid Renewable Energy System (HRES) and the "Power To X" concepts. HRES refers to the combination of two or more renewable energy sources, operating in stand-alone or grid-connected mode [106]. The stand-alone mode is characterized by a decentralized production and large storage capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some advanced technologies are relevant to the renewable energy sector for power generation to achieve optimal efficiency in the renewable energy supply chain, notably the Hybrid Renewable Energy System (HRES) and the "Power To X" concepts. HRES refers to the combination of two or more renewable energy sources, operating in stand-alone or grid-connected mode [106]. The stand-alone mode is characterized by a decentralized production and large storage capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the hybrid renewable energy system can successfully address some of the barriers in terms of flexibility, efficiency, reliability, emissions, and fuel economy [108,109]. To decide the ideal combination, it is important to consider the local availability of resources at a given site, the efficiency of energy conversion, and the land requirements [106]. On the other hand, the "power to X" system allows for a multi-stage production process based on the transformation of power into "X", where X denotes various forms of energy such as heat, hydrogen, gas, liquid, methane, ammonia, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al showed that when retailers have fairness preferences, cooperative advertising strategies can be used to achieve supply chain coordination under certain conditions [30]. Chen et al developed decentralized decision-making models under two types of behavioural concerns-fairness concerns and risk aversionand derived the optimal strategy for each member with a Stackelberg game in which the manufacturer acts as the leader [31]. Guan et al studied manufacturers and retailers with Nash bargaining fairness concerns and used revenue and cost-sharing contracts to achieve supply chain coordination [32].…”
Section: B Supply Chains Under Fairness Preferencesmentioning
confidence: 99%
“…As the greening level expands, it turns out to be progressively expensive. The greening level investment cost is considered as a quadratic function given by λθ 2 (Ghosh and Shah [27], Chen et al [47]). This quadratic function not just captures the phenomenon of expanding marginal expense, yet additionally mirrors the fact that the investment cost of the underlying greening level per unit is diminishing.…”
Section: Assumptionsmentioning
confidence: 99%